Construction court in Malaysia: a legal analysis / Farisha Husna Mat Darus...[et al.] - Mat Darus, Farisha Husna; Kamarudin, Nur Fatin Syakinah; Mazlan, Nurulhuda Najwa; Raja Zainal Abidin, Raja Syaza Farhanah (2014)
The reasoning behind this research is to study the effectiveness and efficiency of the Malaysian Construction Court, which is a new specialist court in the Malaysian legal landscape. As the Construction Court is still in its infancy, this research is carried out in order to provide information on the Construction Court, where previously no information has been made available. Besides that, the research is also carried out in order to see if it is necessary to establish a Construction Court, and if the Construction Court has been effective. A qualitative approach is taken in doing the research. Interviews with the Construction Court judges and the General Manager of Business Division of the Construction Industrial Development Board had been conducted in order to gain relevant information. As the construction industry is increasingly developing, this research may be beneficial to those in the construction industry, and also to those with an interest in construction law. The focus of the research is on the effectiveness and efficiency of the Construction Court in order to determine whether the establishment of the Construction Court is necessary and warranted. An examination of the construction industry in Malaysia prior to the establishment of the Construction Court is made, whereby it was found that the construction industry had faced certain disadvantages which slowed its progression. The disadvantages include the lengthy time take to resolve disputes, inadequate relief, and the insufficiency of dispute resolution provided by civil courts and arbitration. This gave rise to the establishment of the Construction Court, which was the product of like-minded parties including the construction industry and the judiciary. The collaboration occurred in a bit to address the issues that are faced by the construction industry, which may affect adversely the Malaysian economy. Many cases have been filed at the Construction Court since its inception, which can be interpreted^ that there is a demand for a specialist Construction Court. According to the Construction Industry Development Board, out of the 205 cases filed in the Construction Court, 124 cases were disposed by June 2014, meaning that 60.5% of cases were disposed in the period of fifteen months. Based on the number of cases disposed, it can be said that the Construction Court is effective.